2014
DOI: 10.5424/sjar/2014121-4617
|View full text |Cite
|
Sign up to set email alerts
|

Pyrenean meadows in Natura 2000 network: grass production and plant biodiversity conservation

Abstract: In semi-natural mountain meadows, yield and forage quality must be reconciled with plant biodiversity conservation. This study was performed to analyze the relationships between these three parameters. To quantify plant biodiversity and pastoral value (PV), phytosociological inventories were performed in 104 semi-natural meadows in the Central Spanish Pyrenees included in the Natura 2000 network. Forage yields were calculated and forage samples were analyzed for relative feed value (RFV). We identified two mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
0
15
0
2
Order By: Relevance
“…In the burned and dense shrub cover plots the CN ratios are lower, favouring the presence of species with low pasture value: Galium lucidum , Galium verum , Linun suffruticosum , Hieracium gr . Pilosella , Daucus carota , Plantado media , Centaurea jacea (Molinillo et al ., ; Reiné et al ., ). It should also be highlighted that the highest erosion rates recorded in these plots, compared with the grazing meadow plot, involve higher nutrient losses, especially in the burned plot.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the burned and dense shrub cover plots the CN ratios are lower, favouring the presence of species with low pasture value: Galium lucidum , Galium verum , Linun suffruticosum , Hieracium gr . Pilosella , Daucus carota , Plantado media , Centaurea jacea (Molinillo et al ., ; Reiné et al ., ). It should also be highlighted that the highest erosion rates recorded in these plots, compared with the grazing meadow plot, involve higher nutrient losses, especially in the burned plot.…”
Section: Discussionmentioning
confidence: 97%
“…It is interesting to note that the grazing meadow plot shows the highest values of organic matter (5·8%) and CN ratio (10·5). The first values contribute to generating stronger aggregates and increase aggregate stability, reducing soil erosion (Cerdà, ), and the second promotes the expansion of herbaceous species (legumes and grass) with high pasture value: Medicago sativa , Medicago lupulina , Trifolium pratense , Trifolium repens , Festuca rubra , Dactylis glomerata … (Molinillo et al ., ; Reiné et al ., ) (high presence in the grazing meadow plot). It should be noted that CN values close to 10 are optimum to produce good pasture (Lasanta et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has demonstrated that in areas of G. scorpius these are multiplied by 2.2, from 4566 Mj ha -1 to 10,167.3 Mj ha -1 , and in areas of C. laurifolius by 3.1 (from 2435.2 Mj ha -1 to 7628.6 Mj ha -1 ). This is explained by the presence of several plants with high grazing value under the shrub (Reiné et al, 2014). Most of the pasture is produced in spring and autumn, while it decreases in summer, due to higher evapotranspiration and because some plants do not recover after the spring grazing; it also decreases in winter, due to the plant cycle halting.…”
Section: Discussionmentioning
confidence: 99%
“…The use of SI issued from standard international lists provides a rather rapid and effective tool in order to assess the PV in natural areas, which are managed through grazing animals [37,38].…”
Section: Discussionmentioning
confidence: 99%